Potential raw materials for special use vegetable fatty composite mixtures - Isabayev I.; Atamuratova T. (Техника и технология пищевых производств)
The article is devoted to the analysis of modern priorities in the sphere of food industry main branches development. The author identified the most promising of them, in particular, modification of socially significant food products (fats) by means of their combination with traditional and non-traditional plant raw materials having full fat oil and low-oil content as a source of physiologically functional nutrients. Chemical composition of raw materials has been studied to reveal the biological value and food safety. The efficiency of using wheat germ flour as an ingredient of vegetable fatty composite mixtures in bread production is established. The author suggested using composites that consist of germinated wheat product, animal fat, creamy melted butter, palm, soybean and sunflower oils which have balanced fatty acids content. The author justified the relevance of heat treatment of composite mixtures having wheat germ flour content up to 30.0% of the mixture mass at 40–50 °C, more than 30% – up to 70°C during 10–15 min. That will help increase its microbiological purity, reduce the enzymatic action of germ lipase, protease and lipoxygenase, extend the mixtures shelf life up to 45 days. Optimum proportion of wheat germ flour should not exceed 70.0% of the raw material mixtures weight. It was demonstrated that 30,0 to 50,0% of solid fats can be replaced with vegetable oils. There was a positive effect of the developed composites in the amount of up to 5.0% to the quantity of flour according to the recipe on the quality of bread produced from the 1st grade wheat flour.